Pengaruh manajemen laba, CSR, dan Leverage Aggressiveness dengan asimetri informasi sebagai variabel moderasi - Ariesta Amelia Husen; Waluyo Waluyo (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to determine the influence of profit management, corporate social responsibility, and leverage on tax aggressiveness with information asymmetry as a moderation variable. Companies, as taxpayers, and the government has different interests. The government optimizes state revenue on taxes because taxes are one of the significant revenue factors for a country that is used to finance routine expenses and development expenditures. For companies, taxes are a mandatory burden that can reduce net profit, so companies as taxpayers tend to minimize taxes. Companies use these differences in interests as an opportunity to be more aggressive in minimizing taxes. The method used is descriptive research by recording data accompanied by valued numbers and can give an objective picture of the variables to be studied. The population in the study is mining companies listed on the Indonesia Stock Exchange. The sample selection technique used in this study was Purposive sampling, which is 24 companies during a research period from 2017-2019. This study used panel data regression analysis. The results of this study show that profit management and leverage have a significant effect on tax aggressiveness, while corporate social responsibility does not affect tax aggressiveness. In addition, information asymmetry cannot moderate profit management, corporate social responsibility, and leverage to tax aggressiveness.